Social Media and Youth Mental Health (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Social media is widely used by adolescents and has both positive and negative effects on mental health. While it supports communication, self-expression, and access to information, excessive use is associated with anxiety, depression, poor sleep, and low self-esteem. Psychological factors such as social comparison, validation-seeking, and fear of missing out, along with neurological effects like dopamine-driven addiction and stress responses, contribute to these outcomes. Evidence shows that prolonged usage increases mental health risks, particularly among youth. However, mindful and limited use, along with digital literacy and responsible platform design, can help reduce harm and promote well-being.